Perbandingan kualitas layanan berdasarkan kategori restoran : Studi Kasus di Badung Bali - Pawitan, Gandhi; Widyarini, Maria (Jurnal Administrasi Bisnis, 2011)
In service industry, service quality is used as one factor in competition. Culinaryindustry, such as restaurant, bar, cafe, or eatery booth are one dynamic sector intourism world. As a tourist destination either domestic or international, Bali createsa competitive business environment either local or international as well.American restaurant in average shows a higher score in service quality comparewith others. But Indonesian restaurant gives a higher scores in empathy dimension inservice quality. Customer is expecting a good services, especially in culinary industryin sustaining their businesses. The company should look carefully into aspects ofservice quality, hence they can be a winner in the competitive industry.Keywords: Service quality, hospitality management